2020
DOI: 10.1088/1757-899x/862/6/062005
|View full text |Cite
|
Sign up to set email alerts
|

Technology for reducing urease activity in soybeans

Abstract: The main biochemical component of soy is protein, but it contains quite active anti-nutritional substances, such as proteolytic enzyme inhibitors, urease, lectins and others that reduce its nutritional value. This is the main deterrent to the use of soy in raw form for feeding farm animals and widespread use in the food industry. The article deals with the issues of inactivation of anti-nutrient substances using low-frequency ultrasound in water with hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The proteins oxidized by hydrogen peroxide are tightly bound to water in the ultrasonic medium and exhibit hydrophilicity, while applying ultrasonic waves to passivate urease Morgunova et al (2020) used Bacillus natto to inactivate soybean urease activity. By exploring the effects of fermentation parameters such as ratio of water and soybean meal, culture temperature, and inoculation amount on urease activity, the results showed that the ratio of water to material was 5:1, pH was 4.5, initial temperature was 30°C, inoculation amount was 5% and inoculation time was 8 h. The urease activity decreased by 93% when fermentation period was 72 h. Krajewska (2011) on Sporosarcina pasteurii urease and attested that the presence of a 1,4-hydroquinone moiety covalently binds to the thiol group of αCys 322 (corresponding to αCys 592 in JBU), the active residue is located on a movable helical-steering-helical motif (flap), which is critical for catalysis by regulating the transport of substrates and products through the active site cavity (Mazzei et al, 2017) (Figure 6).…”
Section: Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins oxidized by hydrogen peroxide are tightly bound to water in the ultrasonic medium and exhibit hydrophilicity, while applying ultrasonic waves to passivate urease Morgunova et al (2020) used Bacillus natto to inactivate soybean urease activity. By exploring the effects of fermentation parameters such as ratio of water and soybean meal, culture temperature, and inoculation amount on urease activity, the results showed that the ratio of water to material was 5:1, pH was 4.5, initial temperature was 30°C, inoculation amount was 5% and inoculation time was 8 h. The urease activity decreased by 93% when fermentation period was 72 h. Krajewska (2011) on Sporosarcina pasteurii urease and attested that the presence of a 1,4-hydroquinone moiety covalently binds to the thiol group of αCys 322 (corresponding to αCys 592 in JBU), the active residue is located on a movable helical-steering-helical motif (flap), which is critical for catalysis by regulating the transport of substrates and products through the active site cavity (Mazzei et al, 2017) (Figure 6).…”
Section: Physicalmentioning
confidence: 99%
“…Yalcin and Basman (2015) used infrared treatment of urease on soaked soybeans and showed that infrared treatment at 1208 and 1342 W for 15 min was sufficient to reduce the urease activity of soaked soybean samples. Morgunova et al (2020) used low‐frequency ultrasound to treat soybean proteins in aqueous hydrogen peroxide solution and showed that proteins oxidized by hydrogen peroxide bind closely to water in the ultrasound medium, exhibit hydrophilicity, swell, and increase in mass and volume. And ultrasonic waves with a frequency of 20 kHz showed a significant decrease in urease activity after treating soybean in an oxidized solution of hydrogen peroxide at a concentration of 9% for 30 min.…”
Section: Passivationmentioning
confidence: 99%
“…The evaluation of the micronisation quality was conducted by the index of the urease activity in units of ∆pH. It is much easier to determine the urease activity in the beans than the content of the trypsin inhibitors (Ruis 2013;Morgunova et al 2020). If it is necessary to determine the content of the trypsin inhibitors, we can use the functional dependence between the level of the trypsin inhibitors and the urease activity (Ruis 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Parameters used to test the models for adequacy by the F-criterion N -number of experiments in the plan; k´-number of statically significant regression coefficients of the approximating polynomial; n 0 -number of experiments in the centre of the experiment's plan; s ad -the variance of the adequacy; F p -the calculated value of the Fisher test; F T -the tabular value of the Fisher test https://doi.org/10.17221/2/2021-RAEet al 2000;Yalçın and Basman 2015;Zverev and Sesikashvili 2018;Morgunova et al 2020), although the influence of the humidity on the micronisation process was not taken into account in our studies.…”
mentioning
confidence: 99%